ENSINO E APRENDIZAGEM DE DERIVADA NA EDUCAÇÃO MATEMÁTICA A DISTÂNCIA POR MEIO DA METODOLOGIA DA RESOLUÇÃO DE PROBLEMAS - Pinto, Silvia Prietsch Wendt (2010)
New pedagogical proposals seek for better ways of teaching and learning in order to give students the knowledge construction in a comfortable, interesting and meaningful way. This paper is resulted of a qualitative research focused on Distance Mathematics Learning, which adopted the resolution of problems as teaching methodology. This research was conducted with students enrolled in the subject of Calculus A in a Mathematics Teaching Formation Course, at the Distance Learning of UFPel Universidade Federal de Pelotas; these students, proceeding from twenty-two poles in the South, were distributed in five groups of four components each and participated in the Pro-Licenciatura and Brazilian Open University projects, linked to UFPel. The purpose of this research was to build a teaching proposal, in order to investigate the contributions of the problem solving methodology to the learning of the applications of the derivative in tracing graphs of functions and functions derivates in a virtual learning environment, with students of the subject. The results could be verified by collecting data, through participant observation, field notes, analysis of students' production posted in the forums and discussed in chat rooms. It can be concluded that the use of the solving problems methodology contributed to creating a learning environment conducive to the development of activities, even with the limitations of time and distance by using a virtual learning environment.